Evaluation of teaching performance in the virtual teaching-learning environment, from the perspective of the students of the Professional School of Mechanical Engineering - León Velarde, César Gerardo (2021)
The objective of this article is to evaluate the effect that virtual teaching learning generates in the evaluation of teaching performance, from the perspective of the students, of the professional mechanical engineering school. During the development of the research, it has been determined that the planning, communication and overall performance factors of the teaching performance have experienced a positive variation of 63.64%, increasing by 3.8%, when moving from the face-to-face environment to the virtual teaching-learning environment. While the didactic strategies, organization and subject mastery factors have experienced a positive variation of 59.09%, this increase represents 1.92%. Although a positive effect has been generated on teacher performance, it has been determined that, of the 6 factors, it is the Communication factor which has presented the greatest negative variation, being of the total of 22 teachers, 11 who have decreased their qualification.